2016
DOI: 10.1038/srep32864
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the injection and manipulation of magnetic charge states in nanostructures

Abstract: Realising the promise of next-generation magnetic nanotechnologies is contingent on the development of novel methods for controlling magnetic states at the nanoscale. There is currently demand for simple and flexible techniques to access exotic magnetisation states without convoluted fabrication and application processes. 360° domain walls (metastable twists in magnetisation separating two domains with parallel magnetisation) are one such state, which is currently of great interest in data storage and magnonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 39 publications
(47 reference statements)
1
40
0
Order By: Relevance
“…This phenomenon has been observed in previous works, where the local field of the MFM tip was used to manipulate the magnetic charges. 47,48 In this work, the tip stray field serves as a tool to create and enhance the stability of the configurations. The set of images from Fig.…”
Section: Stability Of the Magnetic Configurationmentioning
confidence: 99%
“…This phenomenon has been observed in previous works, where the local field of the MFM tip was used to manipulate the magnetic charges. 47,48 In this work, the tip stray field serves as a tool to create and enhance the stability of the configurations. The set of images from Fig.…”
Section: Stability Of the Magnetic Configurationmentioning
confidence: 99%
“…Upon reaching the island end the ±1/2 defects are free to reach and annihilate each other, unwinding the i-DW to a collinear state and emitting a spin-wave burst down the nanoisland (t = 0.9 ns). The spin-wave burst interacts with the remaining i-DW 39,41,45 , exerting a torque that accelerates it towards the nanoisland bottom (t = 1.3 ns). As the remaining i-DW approaches the nanoisland bottom, it is increasingly magnetostatically attracted to it, further driving acceleration (t = 2.0 ns) until the i-DW unwinds on contact as described above, leaving a DW-free nanoisland magnetized antiparallel to its initial state (t = 2.5 ns) with reversal completed 2 ns after the c-DW reaches the nanoisland.…”
Section: Resultsmentioning
confidence: 99%
“…We have focused here on magnetic reversal of Ising-like nanoelements. Prior studies have demonstrated injection of 360°DWs 41 and Skyrmions using related locally divergent stray fields (magnetic force microscope tips in these cases) in nanostructures and writing states in nanodisks 70 . The DW-based writing method is highly suitable for integration with such writing schemes, offering substantial future scope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reliably accessing more than a handful of microstates beyond simple global field saturation has proved difficult, with either stochastic AC demagnetization protocols or complex rotating field sequences employed [21,22]. Total microstate control via individual nanowire reversal using magnetic force microscope tips has been demonstrated [23][24][25] but is time consuming and is unsuitable for device integration. Considering ASI as an RMC rather than a model system for geometric frustration, it becomes attractive to modify the aspect ratio and hence the shape anisotropy of each nanowire sublattice, forgoing * troy.dion.16@ucl.ac.uk degenerate dipolar interactions for the microstate control afforded by the different coercive fields between each modified sublattice.…”
Section: Introductionmentioning
confidence: 99%